Addressing Culture in the EFL Classroom: A Dialogic Proposal - José Aldemar Álvarez Valencia; Ximena Bonilla Medina (Profile: Issues in Teachers' Professional Development)
Language teaching has gone from a linguistic centered approach towards a lingo-cultural experience in which learning a language goes hand in hand with the understanding of not only the target culture, but the learner's own culture. This paper attempts to describe and reflect upon a collaborative and dialogical experience carried out between two teachers of the Languages Program of Universidad de la Salle, in Bogotá. The bilateral enrichment of such a pedagogical experience helped the teachers to improve their language teaching contexts and prompted the construction of a theoretical proposal to enhance intercultural awareness. It also opened the way for the development of critical intercultural competence in fl (foreign language) learners.